SHALL YOU BE 'UNMARRIED' TO GET A JOB IN INDONESIA? CRITICAL DISCOURSE ANALYSIS OF JOB RECRUITMENT PROCESS IN INDONESIA - Pratama, Hendi (Universitas Sebelas Maret, 2016)
In this article, I look into four job vacancy advertisements published by two state owned enterprise and two private companies. Using critical discourse analysis (CDA), this article focuses on the text implicit discrimination shown in the usage of the term